Stress Intensity Factors for Crack Problems in Bonded Dissimilar Materials - Khairum Hamzah; Nik Mohd Asri Nik Long; Norazak Senu; Zainidin Eshkuvatov (Journal of Engineering and Technological Sciences, 2020)
The inclined crack problem in bonded dissimilar materials was considered in this study. The system of hypersingular integral equations (HSIEs) was formulated using the modified complex potentials (MCP) function method, where the continuity conditions of the resultant force and the displacement are applied. In the equations, the crack opening displacement (COD) serves as the unknown function and the traction along the cracks as the right-hand terms. By applying the curved length coordinate method and the appropriate quadrature formulas, the HSIEs are reduced to the system of linear equations. It was found that the nondimensional stress intensity factors (SIF) at the crack tips depend on the ratio of elastic constants, the crack geometries and the distance between the crack and the boundary.